The Regional Development of Democratization and Civil Society: Transition, Consolidation, Hybridization, Globalization - Taiwan and Hungary - Szabó, Máté (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2018)
Different starting points, similar processes and different outcomes can be identified when comparing East Central Europe and East and South Asia. The two regions face similar global challenges, follow regional patterns of democratization and face crises. In communist times, East Central Europe was economically marginalized in the world economy, while some parts of Asia integrated well in the global economy under authoritarian rule. Europeanization and a favorable external environment encouraged the former communist countries to opt for the Western-style rule of law and democracy. Different external factors helped the Third Wave democracies in Asia, especially South Korea and Taiwan, which benefited from the support of the United States and other global economic, military and cultural partnerships to develop their human rights culture and democracy while facing their totalitarian counterparts, namely the People’s Republic of China and North Korea. The very different positions Taiwan and Hungary have in their respective regions follow from the different capacities of their transformation management since 1988-1989. Taiwan preserved its leading role and stable democracy despite the threat to its sovereignty from the People’s Republic of China. Hungary never had such an influential and problematic neighbor and was ensured security and welfare partnership by the European Union, which Taiwan lacked. While Taiwan was less secure, economic and social conditions were more favorable for democratization than those in Hungary. Hungary, in turn, held a leading position in democratization processes in the period of post-communist transition which was lost during the crisis and conflicts of the last decade (after 2006 and especially since 2010). Despite the fact that liberalization prepared the way for peaceful transition in both countries and resulted in similar processes of democratic consolidation in the 1990s, Hungary joined the ‘loser’ group in its region, whereas Taiwan is among the top ‘winning’ countries in its region. Taiwan at the moment is starting comprehensive reform processes toward enhanced democracy, civil rights and the rule of law, and Hungarian development is criticized by many external and internal analysts as straying from the path of European-style consolidated democracies towards illiberal trends and hybridization. Western global concepts of democratization may help to identify similarities and differences, and compare stronger and weaker factors in the democratic transitions in Asia and Europe within the Third Wave democracies.

Porównanie Europy Środkowej i Wschodniej z Azją Południową pozwala określić ich punkty startu obu regionów, podobne procesy i zróżnicowane wyniki. Oba regiony borykają się z podobnymi globalnymi wyzwaniami, realizują regionalne wzorce demokratyzacji i stają w obliczu kryzysów. W czasach komunistycznych Europa Środkowo-Wschodnia była ekonomicznie marginalizowana w gospodarce światowej, podczas gdy niektóre znajdujące się pod rządami autorytarnymi regiony Azji dobrze zintegrowały się z gospodarką globalną. Europeizacja i sprzyjające otoczenie zewnętrzne zachęciły byłe kraje komunistyczne do wyboru rządów prawa i demokracji typu zachodniego. Inne czynniki zewnętrzne pomogły demokracji „trzeciej fali” w Azji, zwłaszcza w Korei Południowej i na Tajwanie, które skorzystały ze wsparcia ze strony Stanów Zjednoczonych i innych globalnych partnerstw gospodarczych, wojskowych i kulturalnych, pozwalających im rozwinąć swoją kulturę praw człowieka i demokrację, stojąc twarzą w twarz z totalitarnymi odpowiednikami - Chińską Republiką Ludową i Koreą Północną. Odmienne pozycje Tajwanu i Węgier w ich regionach wynikają z różnych zdolności zarządzania transformacją w latach 1988-89. Tajwan zdołał zachować swoją wiodącą rolę i utrzymać stabilną demokrację, pomimo zagrożenia suwerenności ze strony Chińskiej Republiki Ludowej. Węgry nigdy nie miały tak wpływowego i problematycznego sąsiada, a gwarantem ich bezpieczeństwa i partnerstwa w drodze do dobrobytu była Unia Europejska - czynnik nieobecny w Tajwanie. Podczas gdy poziom bezpieczeństwa na Tajwanie był niższy, panujące tam warunki ekonomiczne i społeczne były bardziej korzystne dla demokratyzacji niż na Węgrzech. Węgry z kolei miały wiodącą pozycję w procesach demokratyzacji w czasach postkomunistycznej transformacji, którą utraciły w czasie kryzysu i konfliktów w ostatniej dekadzie (po 2006 r., a zwłaszcza od 2010 r.). Mimo że liberalizacja przygotowała grunt pod pokojowe przemiany w obu krajach i doprowadziła do podobnych procesów demokratycznej konsolidacji w latach 90. dwudziestego wieku, Węgry dołączyły do grupy przegranych w swoim regionie, podczas gdy Tajwan jest jednym z głównych liderów w swoim regionie. Tajwan w chwili obecnej rozpoczyna kompleksowe reformy zmierzające do wzmocnienia demokracji, praw obywatelskich i prawo-rządności, a węgierski rozwój jest krytykowany przez wielu zewnętrznych i wewnętrznych analityków jako odejście od ścieżki demokracji skonsolidowanych typu europejskiego w kierunku nieliberalnych trendów i hybrydyzacji. Zachodnie globalne koncepcje demokratyzacji mogą pomóc zidentyfikować podobieństwa i różnice oraz porównać mocniejsze i słabsze czynniki przemian demokratycznych w Azji i Europie w ramach demokracji trzeciej fali.
Regionalny rozwój demokratyzacji i społeczeństwa obywatelskiego: transformacja, konsolidacja, hybrydyzacja, globalizacja - Tajwan i Węgry
Keywords: democratization; hybridization; regional development; Central Europe; East Asia; Democracy; party system; political protest; social movements; mobilization; authoritarianism; competitive authoritarianism